Role of Communication and Interaction in Enhancing Organisational Performance - Meha, Arbresha (Technium Social Sciences Journal, 2020)
In circumstances of constantly changing concepts related to the organisation as well as the progress of its performance and behaviour, communication has become a focus of many researchers who have consistently analyzed it in relation to organisations of various forms. This study aims to assess the role of communication and interaction in enhancing organisational performance. This study involved 607 respondents employed in banks and insurance companies. The methodology used for this study was the integration of quantitative methods. We have used two instruments in this study, one questionnaire to measure the role of communication and interaction and the other one organisational performance.